2019
DOI: 10.1186/s12985-019-1155-3
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of recombinant Avihepatovirus 3C protease and its localization

Abstract: Background The picornaviral 3C protease mediates viral polyprotein maturation and multiple cleavages of host proteins to modulate viral translation and transcription. The 3C protease has been regarded as a valid target due to its structural similarity among different picornaviruses and minimal sequence similarity with host proteins; therefore, the development of potent inhibitors against the 3C protease as an antiviral drug is ongoing. Duck hepatitis A virus (DHAV) belongs to the Pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…Concerning the aspartyl protease protein family, it presented a high recombination rate that agrees with previous studies (e.g. Speranskaya et al , 2012 ; Sun et al , 2019 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Concerning the aspartyl protease protein family, it presented a high recombination rate that agrees with previous studies (e.g. Speranskaya et al , 2012 ; Sun et al , 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…The results ( Table 1 ) showed that both recombination and substitution rates are heterogeneous among coronavirus protein families and that the aspartyl protease protein family presents a high recombination rate in agreement with previous observations (e.g. Speranskaya et al , 2012 ; Sun et al , 2019 ).…”
Section: System and Methodssupporting
confidence: 90%
“…The procedure was performed as described previously and modification slightly ( Sun et al, 2019b ). Briefly, to construct eukaryotic recombinant plasmids pCAGGS-2B-HA and pCAGGS-FLAG-2B, DHAV-1 genomic RNA was extracted from the culture supernatants of DEF cells that were infected with DHAV-1.…”
Section: Methodsmentioning
confidence: 99%
“…The eukaryotic expression vector pCMV-Myc was purchased from TaKaRa. pCAGGs-VP3-Flag and pEGFP-N1-3C were also stocks in our laboratory (Lai et al, 2019;Sun et al, 2019). Duck-derived G3BP1 gene was cloned into the pEGFP-C2 vector with the DNA Ligation Kit (TaKaRa).…”
Section: Expression Plasmidsmentioning
confidence: 99%